A dark consequence of developmental dyslexia: discrimination of mirror images is not automatized - Leite, Isabel (2019)
Reading is a cultural activity too recent in the history of the humankind to be en- crypted in the human genome but, paradoxically, some people fail to achieve fluent reading, despite adequate instruction and no sensorial or general cognitive deficits that could explain such specific difficulty. Intensive research has been devoted to the neurocognitive mecha- nisms of reading and the putative differences related to this specific developmental reading disorder or dyslexia. Much research has focused on the relation between literacy and oral lan- guage but reading is also an intensive visual activity that requires specific adaptations of the visual ventral system, including the suppression of mirror invariance (the perceptual bias by which one stimulus and its lateral reflection or mirror image, e.g., d and b, are processed as equivalent percepts). Interestingly, reversal errors (e.g., confusing d with b) have long been documented in dyslexia. In the present paper, we review the available evidence regarding mir- ror-image processing in dyslexic children, taking into account the methodological aspects and shortcomings of prior studies. We also revisit our findings with typically-developing children (preliterate children and 1st-grade beginning readers) and adults (illiterate, ex-illiterate, and schooled literate), and dyslexic children and their two control groups (of chronological age, and of reading level). Our research suggests that dyslexic readers fail to acquire the automatic changes promoted by literacy acquisition outside the written domain. More specifically, we argue that mirror-image discrimination, which is triggered by learning to read and occurs au- tomatically in the course of visual object recognition in typically-developing readers, may ne- ver become automatized in dyslexic readers.